Perception of Territorial Brands “Armenia” and “Russia” by the Armenians Living in Armenia and Russia - Asriyan, Elina (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
In order to investigate the perception of the territorial brand of Armenia and Russia among Armenians living in Armenia and Russia, we organized a psychological study. The study involved 100 Armenians male and female, 50 of them were citizens of Armenia, 50 lived in Russia for the past 5-10 years. The conclusion is that in both experimental groups the factors determining the preference of the territorial brand of the Republic of Armenia are mainly conditioned by the emotional and value-based motives (homeland, ancient culture, sustainable values, etc.). And the preference for the territorial brand of the Russian Federation is based on the motives acting at a rational and functional level.